2002
DOI: 10.1111/j.1651-2227.2002.tb00107.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental profiles and auditory perception in 25 children attending special preschools for language‐impaired children

Abstract: Aim: To study different developmental profiles and auditory perception in a representative group of children with language impairment (LI). Methods: A multidisciplinary investigation was carried out in a group of 25 children attending units specifically for language‐impaired children. An assessment of the cognitive level, motor performance, behaviour and auditory perception was performed and the results were compared with those for age‐matched groups of children. Results: Among those with moderate or severe la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 22 publications
2
24
0
2
Order By: Relevance
“…Several researchers have questioned the SLI term (e.g. Sahlén & Nettelbladt, 1995, Bates, 2002, Fernell et al 2002, Ors, 2002, because children with language impairment usually also show other subtle cognitive or neurodevelopmental disabilities. However, when other studies are referred to, the terminologies used by the original researchers have been kept.…”
Section: Terminologymentioning
confidence: 99%
See 3 more Smart Citations
“…Several researchers have questioned the SLI term (e.g. Sahlén & Nettelbladt, 1995, Bates, 2002, Fernell et al 2002, Ors, 2002, because children with language impairment usually also show other subtle cognitive or neurodevelopmental disabilities. However, when other studies are referred to, the terminologies used by the original researchers have been kept.…”
Section: Terminologymentioning
confidence: 99%
“…had LD combined with other disabilities within the neuropsychiatric and/or neurodevelopmental spectrum at a follow-up at school-start. In a study of children attending a Swedish language preschool (Fernell et al, 2002), 20 out of 23 (87%) children with moderate or severe LI were identified with associated developmental problems such as motor, cognition and/or behavioural problems. In a more recent study by Rejnö-Habte Selassie et al (2005) a higher proportion of attention and motor problems, EEG abnormalities and epileptic syndromes were found in children with severe language disorders than in the general population.…”
Section: Co-existence Between Language Impairment and Neuropsychiatrimentioning
confidence: 99%
See 2 more Smart Citations
“…3 ], but other authors have since failed to replicate these findings [4][5][6][7][8] . Associations between the Rapid Auditory Test and reading abilities have been identified [9] , but none have been shown to exist for language skills [10,11] .…”
mentioning
confidence: 60%